Kinetic and kinematic determinants of female sprint performance - Gleadhill, S.; Nagahara, R. (Journal of Sports Sciences, 2021)
This study elucidated spatiotemporal and ground reaction force determinants of running speed and acceleration for female sprinters during the entire sprinting. Fifteen female sprinters completed 60 m sprints. Kinematic and kinetic variables were measured using force platforms over a 50 m distance from the start. Results demonstrated that higher step frequency (11th-27th steps, r = 0.517-0.717) through shorter support time (12th-27th steps, r = -0.535 to -0.634) could be determinants of running speed. Moreover, increasing step length (1st-10th steps, r = 0.550-0.938), suppressing increases in step frequency (2nd-7th steps, r = -0.639 to -0.870), suppressing decreases in support time (1st-5th steps, r = 0.599-0.709) and increases in flight time (4th-7th steps, r = 0.523-0.649) can be essential for greater running acceleration. Propulsive mean force (1st-5th steps, r = 0.663-0.876) and anteroposterior net mean force (all steps, r = 0.697-0.894) are likely determinants of greater running acceleration. At the maximal speed phase there was no correlation between running speed and the other variables. Differences with previously found male sprint determinants suggest that training targets specific to female sprinters are necessary for improving training designs and race strategy.